Environmental Performance of Grazing Beef Cattle Systems in the Well- Drained Neotropical Savannas of Colombia: A Review of Results from Modelling Research - Ramírez Restrepo, Carlos Alberto; Vera Infanzón, Raul R.; Rao, Idupulapati M. (2019)
This paper is based on results obtained on live weight (LW) dynamics and it reviews the carbon (C) footprint of cattle- pasture systems where cattle were experimentally tested following representative commercial farming practices in the Colombian well-drained native neotropical savannas. We found that the derived carbon dioxide-equivalent efficiency indices, generated from modelling efforts, could explain the observed variation in LW fluxes related to cattle categories, animal physiological stages and specific farming conditions.